Prostaglandins and prostaglandin synthetase inhibitors regulate the synthesis of complement components by human monocytes. - Lappin, D F (1982)
The addition of prostaglandins E2 (PGE2), PGD2, PGI2, 6-keto PGF1 alpha and thromboxane B2 (TXB2) to human monocyte cultures, inhibited the production of the second component of complement (C2). PGF2 alpha did not significantly affect C2 production. As the former compounds, but not the latter increase intracellular cAMP, it was thought that the effect was mediated by this action. The addition of cyclo-oxygenase and lipoxygenase inhibitors to monocyte cultures enhanced the synthesis of complement components and other proteins in a dose-dependent fashion: cyclo-oxygenase inhibitors being more potent in this regard than lipoxygenase inhibitors. The enhancing effect of cyclo-oxygenase inhibitors paralleled their ability to inhibit cyclo-oxygenase activity. The enhancement of C2 synthesis by the addition of cyclo-oxygenase and lipoxygenase inhibitors was reversed by the addition of PGs to the cultures. It is concluded that the production of PG by monocytes could provide an endogenous mechanism to control the synthesis of complement components and other proteins.